2008
DOI: 10.1682/jrrd.2007.06.0083
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms in Bosnian refugees 3 1/2 years after resettlement

Abstract: Abstract-This study describes the evolution of trauma-related symptoms over 3 1/2 years in a group of Bosnian refugees. Twenty-one refugees received standardized psychological assessments shortly after arriving in the United States and then 1 year and 3 1/2 years later. Of these refugees, 76% met diagnostic criteria for posttraumatic stress disorder (PTSD) at baseline, 33% at 1 year, and 24% at 3 1/2 years. PTSD severity scores in women refugees were higher than scores in men at all three evaluation time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
2
19
1
2
Order By: Relevance
“…This is in line with research that describes the evolution of trauma-related symptoms over three and a half years among Bosnian refugees resettled to the United States (Vojvoda et al, 2008). No correlation was established between PTSD symptom severity and people's age or level of trauma exposure, but it showed that women were more affected than men.…”
supporting
confidence: 87%
“…This is in line with research that describes the evolution of trauma-related symptoms over three and a half years among Bosnian refugees resettled to the United States (Vojvoda et al, 2008). No correlation was established between PTSD symptom severity and people's age or level of trauma exposure, but it showed that women were more affected than men.…”
supporting
confidence: 87%
“…Firstly, organized violence may result in repetitive and extended traumatic stress followed by high rates of posttraumatic stress disorder (PTSD) [1,2,3,4,5]. Secondly, a large proportion of survivors of war and torture become internally displaced people, refugees, or asylum seekers, which involves a variety of additional and potentially continuous stressors in everyday life [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among research concerned with people with a refugee background, a bulk of studies can be found focusing on the negative health effects of war and hardships on people. This pattern is also found in research concerning people who have gone through resettlement (Morris et al 2009;Beiser 2009;Beiser & Flemming 1986;Vojvoda et al 2008;Söndergaard 2002, Marshall et al 2005Museru et al 2010;Huijts et al 2012;Suleiman-Hill & Thomp-son 2011;Lindencrona et al 2008;Teodorescu et al 2012;Blight 2009;Ghazinour et al 2004). This research stretches from the time of arrival in the new country, to studies looking at health aspects of resettled people who have been living in the resettlement country for decades.…”
Section: Refugees and The Focus On Mental Health And Ptsdmentioning
confidence: 53%